AgSCF3 Radical Addition Based on an Oxidant-Free α,β-Amide (Trifluoromethyl)sulfanylation Reaction - Li, Zhi-Bo; Zhang, Jin; Shi, Yi-Ran; Li, Hong; Yang, Min-Ge; Zhu, Wen-Qing; Fan, Qiang-Wei; Li, Yang (Synlett, 2024)
(Trifluoromethyl)sulfanylamides are an important class of organic compounds that are common among natural products and drug molecules. Here, we report a (trifluoromethyl)sulfanylation reaction using silver(I) (trifluoromethyl)sulfide as a free-radical (trifluoromethyl)sulfanylation reagent for β-amide compounds. This reaction does not require stoichiometric oxidants or additional transition-metal catalysts, and can be achieved by adding common organic acids. This method has excellent applicability and can accommodate several functional groups, including ester groups, acyl groups, and even bromo or iodo groups. Heterocyclic α,β-amides can also be readily converted into the corresponding products. This reaction also provides a new method for the synthesis of deuterated (trifluoromethyl)sulfanylamides.
Keywords: (trifluoromethyl)sulfanylation; acid catalyst; amides; free-radical reaction; silver AgSCF3